Erosive Potential of Commercially Available Candies - Maghata Lazzaris; Maria Mercês Aquino Gouveia Farias; Silvana Marchiori Araújo (Association of Support to Oral Health Research (APESB), 2015)
Objective: To measure the acidity of commercially available candies. Material and Methods: Tic Tac® candies with the following flavors were selected: mint, orange, extra-strong, cinnamon, strawberry, cherry/passion fruit, acquired in supermarkets. Candies were triturated and from the resulting powder, 3 samples of 5 grams were separated and dissolved in 10ml of doubly deionized water. This process has allowed reading pH in triplicate, measured with the aid of an in vitro combined potentiometer and electrode, previously gauged with pH 4 and 7 with standard solutions before reading. In candies with pH values under 5.5.pH, tritatable acidity was verified. Three 15-gram candy powder samples were separately dissolved in 30 ml of doubly deionized water. In this solution, aliquots of 100 μl 1N NaOH were added to reach pH 5.5. Mineral water was used as control. The results were submitted to Analysis of Variance (ANOVA). The comparisons of means were carried out by the Tukey test at 5% significance level (p<0.05). Results: Only orange (pH 2.17), cherry/passion fruit (pH 2,26) and strawberry flavors (pH 2.46) have shown pH values under the critical point for enamel dissolution, significantly diverging from control and the other flavors. The volume of 1N NaOH used to raise the pH to 5.5 ranged from 2,000 to 2,800 μl, and the strawberry flavor has presented the highest tritatable acidity, significantly differing from the others. Conclusion: Candies of orange, cherry/passion fruit and strawberry flavors presented erosive potential and their frequent consumption can contribute to the development of dental erosion.